2009
DOI: 10.1590/s0100-40422009000700036
|View full text |Cite
|
Sign up to set email alerts
|

Exposição humana a substâncias químicas potencialmente tóxicas na dieta e os riscos para saúde

Abstract: Recebido em 16/9/08; aceito em 11/2/09; publicado na web em 23/7/09 CHEMICAL DIETARY EXPOSURE AND THE RISKS TO HUMAN HEALTH. Humans are exposed to a variety of chemicals from the consumption of food, including undesirable compounds such as pesticides and mycotoxins. Chemical human risk assessment is a process intended to estimate the risk to a given population from the exposure to a chemical (or to a chemical group having the same mechanism of action). The process consists of four steps, namely hazard identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
11
0
12
Order By: Relevance
“…It is worthwhile to point out that their contribution to health risk, even for the more sensible consumers, was not significant. Jardim and Caldas (2009) attributed the differences in the ADI values between national and international data for some substances, as observed in this study (azinphos-methyl, carbaryl and carbendazim) to the differences in the toxicological criteria employed during the evaluation process by the governmental agencies. A surpass on ADI parameter does not represent pesticide residues above the MRL.…”
Section: Resultsmentioning
confidence: 67%
“…It is worthwhile to point out that their contribution to health risk, even for the more sensible consumers, was not significant. Jardim and Caldas (2009) attributed the differences in the ADI values between national and international data for some substances, as observed in this study (azinphos-methyl, carbaryl and carbendazim) to the differences in the toxicological criteria employed during the evaluation process by the governmental agencies. A surpass on ADI parameter does not represent pesticide residues above the MRL.…”
Section: Resultsmentioning
confidence: 67%
“…Point estimates are generally considered to be most appropriate for screening purposes and are commonly used as a first step in exposure assessments because they are relatively simple and inexpensive (KROES et al, 2002;DORNE et al, 2009;JARDIM;CALDAS, 2009). However, inherent in the point estimate models are the assumptions that all individuals consume the specified foods at the same amount, that the contaminant is always present in the foods at an average/high concentration, and that all individuals have the same body weight.…”
Section: According Tomentioning
confidence: 99%
“…6:4 Studies have shown that dyes can cause adverse health effects, such as food hypersensitivity, some types of cancer, hyperactivity Disorder, Hyperactivity Attention Deficit (ADHD), among others. [8][9] Although the dye is capable of causing adverse health effects, they are large-scale additives used by the food industry. 7,[10][11] Given the above, this study aims to describe the food dyes present in the ultra-processed foods consumed by college of nutrition course at a public university of Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%